LAPORAN TUGAS AKHIR PERAN PRODUSER DALAM FILM DOKUMENTER "DI BAWAH ATAP: ANTARA KELUARGA DAN POLITIK" - Cindy Olivia Graciella (2023)
The final report of this work was carried out with the aim of discussing the role of the producer in making the documentary film "Under the Roof: Between Family and Politics" by using the theory of liberal feminism which focuses on the assertion that every human being has equal rights without exception, including women as individuals who are equal to men and have full space and freedom in the world of politics. This documentary film was made with the aim of providing an overview of the role and position of women in the world of politics by looking at the circumstances and situation in Indonesia. The role and position of women in the world of politics certainly requires a much extra struggle compared to men. This is due to the dominant social views in society where the role of women in politics in Indonesia is minimal. The most important thing from the producer's role is being able to pay attention to three aspects, namely management related to time and internal and external parties. Finance related to production funds, accountability for production funds in writing, as well as each party involved in production funds. And the last is marketing, namely the marketing strategy carried out in the screening of documentaries so that the message can be conveyed optimally according to the target audience